Catalyst- and solvent-free hydrophosphination and multicomponent hydrothiophosphination of alkenes and alkynes. Issue 18 (6th June 2016) - Moglie, Yanina; González-Soria, María José; Martín-García, Iris; Radivoy, Gabriel; Alonso, Francisco
Abstract : The hydrophosphination and hydrothiophosphination of alkenes and alkynes are accomplished in the absence of a solvent and a catalyst in a regio- and stereoselective manner. Abstract : The hydrophosphination of carbon–carbon multiple bonds has been generally performed under acid, base or metal catalysis in different solvents. Herein, alkyl and alkenyl tertiary phosphines are obtained by the addition of diphenylphosphine to alkenes and alkynes, respectively, in the absence of a solvent and a catalyst. In the presence of elemental sulfur, the corresponding alkyl and alkenyl tertiary phosphine sulfides are synthesized in a three-component process. These simple methods, which meet most of the principles of Green Chemistry, are highly regioselective towards the anti-Markovnikov products and diastereoselective towards the Z alkenyl phosphines. The mechanistic aspects of the reactions are also tackled and the efficiency of the latter is compared with that of the catalytic methods.